Care in Chronic Diseases and in "Frail" Patients in General Practice - Lucio, Mango (International Journal of General Practice, 2020)
The world of chronicity is an area in progressive growth that involves a considerable commitment of resources, requiring continuity of assistance for long periods of time and a strong integration of health services with social ones and those requiring residential and territorial services often not sufficiently designed and developed. The fundamental aim of the treatment of chronic systems is to keep as much as possible the patient at home and prevent or reduce the risk of institutionalization. GP could put their expertise to good use in the Complex of Primary Care Units and Territorial Functional Aggregations, reducing the costs of the health service.
Keywords: chronic diseases; GP assistance; domiciliary care